Post-transplant lymphoproliferative disorder in adult renal transplant recipients: survival and prognosis. Issue 2 (1st February 2016) - Morton, Muir; Coupes, Beatrice; Ritchie, James; Roberts, Stephen A.; Klapper, Paul E.; Byers, Richard J.; Vallely, Pamela J.; Ryan, Kate; Picton, Michael L.
Abstract : Post-transplant lymphoproliferative disorder (PTLD) is a rare, serious complication following solid organ transplantation, with an incidence of 2.6 cases per 1000 patient years. Optimal treatment strategies and risk stratifications specific to kidney transplantation are lacking and PTLD mortality remains high. This study investigated survival and prognosis in 89 cases of PTLD presenting over 44 years at Manchester Royal Infirmary. Patient survival following diagnosis was 72% at 6 months, 67% at 1 year and 54% at 3 years. In multivariate analysis, a poorer 3 year survival was associated with acute kidney injury at diagnosis ( p = 0.0001), impaired renal function ( p = 0.04), early onset ( p = 0.02), T cell disease ( p = 0.02) and previous treatment with anti-thymocyte globulin ( p = 0.04). The inclusion of graft function adds prognostic value to risk stratification and should be explored further. Strategies to improve survival should include timing and choice of immuno-chemotherapy, preparation for dialysis and aggressive surveillance for sepsis and treatment toxicity.